Types and manifestations of gender-based violence: a visibility based on stories of female victims in Soacha, Colombia - Tibaná-Ríos, Diana Carolina; Arciniegas-Ramírez, Diana Alejandra; Delgado-Hernández, Ingrid Julieth (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This article is a result of a research study titled "Gender-Based Violence against Women, Girls and Adolescents, in the Context of Domestic Violence: An Analysis Based on the Stories contained in the files of the Second Family Police Station in Soacha". Two hundred and seventy-seven case files of protection measures granted in 2017 were reviewed. These files contain the narration of the facts from the perspective of the complainant or victim; once the sample has been selected, by means of the documentary research technique, the information is gathered and later the use of language is examined through discourse and content analysis, highlighting the different types and manifestations of gender violence. The results make it possible to identify that the stories of female victims do not only give account of domestic violence, but that there is a background of types and manifestations of violence typical of gender-based violence.